Menelaah Keadilan dalam Kebijakan Penanggulangan Illegal Fishing Di Indonesia: Perspektif Konsep Keadilan Thomas Aquinas - Mashuril Anwar; Rini Fathonah; Niko Alexander (Faculty of Law, Universitas Pattimura, 2021)
Justice is still an expensive item that is difficult to reach by every level of Indonesian society, including local fishermen who do illegal fishing. The criminal law policy in tackling illegal fishing which is represented in the Fisheries Law is not proportional and does not have a clear measure. Therefore, in the case of illegal fishing, a discourse of justice is attached. Related to the concept of justice offered by Thomas Aquinas, which emphasizes equality, justice, and the policy of tackling illegal fishing in Indonesia, it is interesting to discuss. This article aims to examine funds to analyze the concept of Thomas Aquinas 'philosophy of justice and to explore justice in the policy of tackling illegal fishing in the perspective of Thomas Aquinas' philosophy of justice. In order to answer these problems, this study uses a normative juridical method. Based on the research results, the concept of justice offered by Thomas Aquinas consists of distributive, commutative, and indicative justice. The essence of Thomas Aquinas' three concepts of justice is proportional to equality. Associated with Thomas Aquinas' concept of justice, the policy to combat illegal fishing in Indonesia has not provided justice. It is said that because the sanction for deprivation of freedom in the Fisheries Law only applies to local fishermen and has not reached foreign fishermen who do illegal fishing. In order to be fair, the sanction of deprivation of liberty should not apply to local fishermen who do illegal fishing as well as foreign fishermen.